Trichuris muris as a tool for holistic discovery research: from translational research to environmental bio-tagging. Issue 14 (6th December 2021) - Mair, Iris; Else, Kathryn J.; Forman, Ruth
Abstract : Abstract: Trichuris spp. (whipworms) are intestinal nematode parasites which cause chronic infections associated with significant morbidities. Trichuris muris in a mouse is the most well studied of the whipworms and research on this species has been approached from a number of different disciplines. Research on T. muris in a laboratory mouse has provided vital insights into the host–parasite interaction through analyses of the immune responses to infection, identifying factors underpinning host susceptibility and resistance. Laboratory studies have also informed strategies for disease control through anthelmintics and vaccine research. On the contrary, research on naturally occurring infections with Trichuris spp. allows the analysis of the host–parasite co-evolutionary relationships and parasite genetic diversity. Furthermore, ecological studies utilizing Trichuris have aided our knowledge of the intricate relationships amongst parasite, host and environment. More recently, studies in wild and semi-wild settings have combined the strengths of the model organism of the house mouse with the complexities of context-dependent physiological responses to infection. This review celebrates the extraordinarily broad range of beneficiaries of whipworm research, from immunologists and parasitologists, through epidemiologists, ecologists and evolutionary biologists to the veterinary and medical communities.